A new e-commerce model for free-riding behavior in decentralized supply chains - Andreea Marin-Pantelescu; Alina Constantinescu; Mihai Daniel Roman; Adela Socol; Lidija Kraujalienė (Journal of Business Economics and Management)
The complexity of consumer free-riding behavior is a current significant problem, as modern online purchasing channels sharply compete with the traditional ones. The purpose of this study is to examine the impact of showrooming behavior by free-rider consumers on product valuation within a decentralized supply chain. Also, we examine how the consumers’ use of the benefits of the experience achieved in the offline channel to buy from the online channel influences their product valuation in a decentralized supply chain and influences the profits’ level of offline retailers. We develop an e-commerce model for product valuation when customers visit a brick-and-mortar unit for products and then buy them online. Results have indicated that the free-riding customers’ product valuation is between online and offline customer product valuations and the price at which the customer becomes a showrooming customer is influenced not only by the offline price, but also by the degree of the online channel acceptance and the shopping services value factor. This study has managerial consequences in decision-making of sellers, especially for traditional stores which to maximize the profit must optimize the offline additional services, to reduce the phenomenon of free-riding and at the same time not to generate additional costs.